Penjelasan Epistemologi Islam dan Perbandingannya dengan Epistemologi Barat - Almadani, Muhammad Zaqi; Prawira Hadi, Narendra Yudha; Arthana, Daffo Yusuf; Waffiudin, Moch. Danish; Muhammad, Albian Gustav; Al-ikhsan, Muhammad Fachri; Kurniawan, Taufiq (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Epistemology, as a theory of knowledge, is the foundation of every scientific tradition in understanding the nature of truth, the sources of knowledge, and the methods of its validation. This article examines the fundamental differences between Islamic and Western epistemology through a literature review approach and a critical analysis of contemporary literature. In Islamic epistemology, revelation is positioned as the highest, absolute source of knowledge, while reason and experience serve as instruments for interpreting and strengthening human understanding. In contrast, modern Western epistemology rests on rationalism, empiricism, and criticism, emphasizing the independence of reason and empirical verification as the basis of scientific truth. These paradigm differences result in different orientations of science: Islamic epistemology integrates moral, spiritual, and rational aspects holistically, while Western epistemology tends to be secular and technocratic. This analysis shows that the dominance of the Western paradigm in modern science has created an ethical and spiritual gap, while Islamic epistemology offers an integrative framework that is more humane and oriented towards the welfare of the people. This article concludes that the integration of the two epistemologies can provide a solution to the problems of contemporary scientific development, particularly in building a science that is methodologically advanced but remains rooted in moral values and transcendental dimensions.